Análisis socioeconómico de los propietarios de microemprendimientos de la calle Isidro Acurio y Avenida Jaime Roldós del cantón Milagro, provincia del Guayas - Miranda Pastuzo, Marco Eliseo (2023)
The present investigation focuses on the owners of micro-enterprises in the Milagro canton, where a lousy socioeconomic level could be observed due to several factors focused on the mismanagement of administrative functions as well as external limitations that prevent their development. The purpose of this project was to analyze the socioeconomic situation of the owners of microenterprises. As part of the research methodology, both qualitative and quantitative were applied because measurable and non-measurable data were handled. Within the main result, it was evidenced that despite being businesses without a large organizational structure, they usually generate moderate income for their owners. However, if managed properly, you can have a higher income. In addition, it is necessary to take action on the matter and be able to provide aid programs to the owners of micro-enterprises so that in this way they can grow economically. Finally, it was concluded that the appropriate strategies for the owners of micro-enterprises in order to increase their socioeconomic level, it was considered to generate talks to all the owners of micro-enterprises for the correct management of resources. in addition to creating an association between all the owners of micro-enterprises.